High prevalence of baseline Non-R5 viral tropism in PLWH is associated with immune damage: a systematic review and meta-analysis - Liu, Yangyang; Yuan, Defu; Yin, Yueqi; He, Qian; Zhao, Meng; Ma, Hongfei; Wei, Pingmin; Ge, You (Frontiers in Immunology, 2025)
ObjectiveThis systematic review and meta-analysis aims to characterize the distribution of HIV-1 viral tropism at diagnosis among people living with HIV (PLWH) and examine its association with baseline CD4+ T lymphocyte counts, thereby providing an evidence base for optimizing clinical interventions.MethodObservational studies reporting viral tropism prevalence and/or baseline CD4+ T cell counts stratified by tropism were retrieved from PubMed, Web of Science, Embase, and Cochrane Library. A random-effects model was employed for pooled prevalence estimation and mean difference calculation. Heterogeneity was quantified using I² statistics, with subgroup analyses and sensitivity tests to identify heterogeneity sources.Results27 articles (N = 9372) were included in this study to analyze the distribution of viral tropism, and the prevalence of Non-R5 tropism was 15.68%. Subgroup analysis showed that the prevalence of Non-R5 IDU (27.86%) was significantly higher than that of sexual transmission (15.29%) and other routes (4.62%). The prevalence of Non-R5 tropism in the CRF01_AE subtype group (30.02%) was significantly higher than that of the B subtype (15.33%) and other subtypes (3.44%) (P ≤ 0.05). A comparison of CD4+ T cell counts (17 articles) showed a difference of −97.77 cells/μL for the Non-R5 tropic group relative to the R5 group.ConclusionOur study find that PLWH with Non-R5 virus had more severe immune damage at diagnosis compared to PLWH with R5 virus. This can update the baseline status of patients in clinical practice. since this is a cross-sectional study, future cohort studies should be conducted to verify the relationship between tropism and changes in immunological indicators.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251088996.